Exchange Rate Pass-through in South America: An Overview - Eduardo Borensztein; Virginia Queijo von Heideken (Inter-American Development Bank (IDB), 2016)
The effectiveness of exchange rate adjustments depends critically on the extent to which depreciations "pass through" to inflation, an effect that is known as exchange rate pass-through (ERPT). In particular, if an exchange rate depreciation does not result in a lasting change in relative prices, namely a real depreciation, it will not provide the desirable competitiveness gains. This paper looks at the question of pass-through and its determinants for the group of countries whose central banks are members of the Financial Stability and Development (FSD) network. All of these countries experienced large terms of trade shocks and large depreciations in the past couple of years. The findings are that ERPT in the FSD countries is moderate and has become lower over time, in line with the international experience. The pass-through moderation has benefitted from the adoption of floating exchange rates and especially an increase in monetary policy credibility. Despite the relatively lower ERPT in the past two decades, the exchange rate continues to be a large determinant of inflation in several countries.
hdl:11319/7779
Keywords: E31; E44; E50; F31; F41; 330; Exchange rate pass-through; Inflation; Depreciation